2012
DOI: 10.3109/07420528.2012.719958
|View full text |Cite
|
Sign up to set email alerts
|

Search for Seasonal Rhythmicity of Pineal Melatonin Production in Rats Under Constant Laboratory Conditions: Spectral Chronobiological Analysis, and Relation to Solar and Geomagnetic Variables

Abstract: Earlier we reported that in a number of experiments pineal melatonin production in rats under constant laboratory conditions displayed seasonal rhythms but subsequently were not always able to confirm this. Since there was no indication under which conditions such rhythms may be present, we performed four consecutive identical experiments with untreated female Sprague-Dawley rats within the same animal room during 1997-2006. Nocturnal urine samples (19-23, 23-3, 3-7 h) were collected at monthly intervals over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…These results highlight a possible involvement of non-photic cues and give hypothetical support to a seasonal Zeitgeber function of the horizontal intensity H of the geomagnetic field that shows circannual variations. Additionally, the 11-years’ sunspot cycle also drives geomagnetic disturbances and could facilitate seasonal 6-sulfatoxymelatonin rhythmicity during specific years 54 55 . Interestingly, in our study CBV showed a clear trough after the solar maximum (1999–2002), at a time when geomagnetic disturbances were maximal during the last solar cycle.…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight a possible involvement of non-photic cues and give hypothetical support to a seasonal Zeitgeber function of the horizontal intensity H of the geomagnetic field that shows circannual variations. Additionally, the 11-years’ sunspot cycle also drives geomagnetic disturbances and could facilitate seasonal 6-sulfatoxymelatonin rhythmicity during specific years 54 55 . Interestingly, in our study CBV showed a clear trough after the solar maximum (1999–2002), at a time when geomagnetic disturbances were maximal during the last solar cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the participants belonged to the same occupational group and military setup, their lifestyle, diet, and exercise protocols were the same with similar physical characteristics. Further, the studies by Bartsch et al (1994Bartsch et al ( , 2010Bartsch et al ( , 2012aBartsch et al ( , 2012b have indicated the possible influence of the natural environment with respect to changes in solar activity through the 11-years sunspot cycle which, might cause geomagnetic disturbances by altering the direction and intensity of the horizontal magnetic field component and thereby controlling the upshots of man-made EMF experiences on health, survival and melatonin rhythm as well. The authors have therefore stressed the importance of year and season in endocrine research regardless of the homogenous environmental conditions negligence of which Int J Radiat Biol Downloaded from informahealthcare.com by Gazi Univ.…”
Section: Discussionmentioning
confidence: 96%
“…Experiments conducted on female laboratory rats over a 2-year-period indicated that the urinary excretion of 6-sulfatoxymelatonin (aMT6s) displays a seasonal rhythm and it was hypothesized that this rhythm is related to the geomagnetic field, which may act as a seasonal zeitgeber (Bartsch et al, 2012a). These authors suggested that the 11-year-sunspot cycle causes geomagnetic disturbances that probably facilitate seasonal aMT6s rhythmicity (Bartsch et al, 2012b).…”
Section: Discussionmentioning
confidence: 98%